Rancangan Bangun Frontend Sistem Layanan Kepakaran Dosen Berbasis Web Menggunakan Framework Yii2 (Studi Kasus : Universitas Jenderal Soedirman) - Priyatini, Priyatini; Briandoko, Singgih; Andayani, Mury (Teknikom: Teknologi Informasi, Ilmu Komputer dan Manajemen; Vol 10 No 1 (2025), 2025)
The development of information technology encourages universities to provide efficient digital services. One essential need is an expert information system that allows quick and accurate access to lecturers' expertise data. This study designs the frontend of such a web-based system using the YII2 Framework, with a case study at Universitas Jenderal Soedirman. The system was developed using the waterfall method, starting from requirements analysis to testing. It includes two main dashboards: a user dashboard (accessible without login) and an admin dashboard (with authentication). Key features include search by name or expertise, category navigation, and data management by administrators. The result is a responsive and user-friendly system interface. It is expected to improve accessibility and transparency of lecturers’ expertise information within Universitas Jenderal Soedirman.